2009
DOI: 10.1186/1752-1947-3-6798
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral synchronous occurrence of three different histological types of renal tumor: a case report

Abstract: IntroductionRenal cell carcinomas account for 85% of all renal neoplasms. With the introduction of modern imaging modalities, there has been an increased diagnosis of renal tumors. Recent studies have shown that partial nephrectomy can be as safe as radical nephrectomy for smaller renal tumors. Renal cell carcinomas are usually unilateral, however, they can be bilateral in 2% to 4% of sporadic cases and considerably more common in familial cases.Case presentationIn this case report, we describe an unusual case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Both types of tumors express differentiation to intercalated cells of the collecting duct system [33] and some authors consider the group oncocytoma/CRCC as a spectrum from benign (oncocytomas) to malignant neoplasm (CRCC) [5]. Both types of neoplasms and mixed forms may be found in oncocytomasis and Birt-Hogg-Dubbe syndrome [4,5,34]. Morphologic and morphogenetic hybrid variants of these tumors are currently being reported [35][36][37][38], most of them with a very favorable prognosis [6,39].…”
Section: Discussionmentioning
confidence: 95%
“…Both types of tumors express differentiation to intercalated cells of the collecting duct system [33] and some authors consider the group oncocytoma/CRCC as a spectrum from benign (oncocytomas) to malignant neoplasm (CRCC) [5]. Both types of neoplasms and mixed forms may be found in oncocytomasis and Birt-Hogg-Dubbe syndrome [4,5,34]. Morphologic and morphogenetic hybrid variants of these tumors are currently being reported [35][36][37][38], most of them with a very favorable prognosis [6,39].…”
Section: Discussionmentioning
confidence: 95%
“…Mukai et al[ 13 ] reported “Synchronous bilateral chromophobe renal cell carcinoma: A case report” in 2009. Radopoulos et al[ 14 ] reported a case of a 57-year-old male patient with two bilateral synchronous chromophobe RCCs accompanied by an oncocytoma and an angiomyolipoma. The patient was treated with open partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this condition has been on the rise due to the increased utilization of ultrasonography and CT scans for evaluating patients with varying clinical presentations [ 4 , 5 ]. Bilateral tumors, either synchronous or asynchronous, have been reported in 2-4% of sporadic cases [ 6 ]. The ccRCC is responsible for 60-75% of unilateral RCC cases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%